2018
DOI: 10.2214/ajr.17.18342
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel Incoherent Motion MRI of Rectal Cancer: Correlation of Diffusion and Perfusion Characteristics With Prognostic Tumor Markers

Abstract: IVIM-DWI-derived parameters in patients with rectal cancer, especially the pseudodiffusion coefficient, are associated with tumor grade and tumor stage and show statistically significant differences between subjects with EMVI and those without EMVI. IVIM-DWI-derived parameters would be helpful in predicting tumor aggressiveness and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 49 publications
6
49
0
Order By: Relevance
“…Some studies looked at more advanced DWI parameters derived from IVIM imaging (discussed in more detail in section on "Recent advances" below). 102,108 Higher IVIM perfusion related parameters were associated with poorer TN-stage, differentiation grade, lymphovascular invasion and extramural venous invasion.…”
Section: Dwi For Follow Up After Treatmentmentioning
confidence: 94%
See 1 more Smart Citation
“…Some studies looked at more advanced DWI parameters derived from IVIM imaging (discussed in more detail in section on "Recent advances" below). 102,108 Higher IVIM perfusion related parameters were associated with poorer TN-stage, differentiation grade, lymphovascular invasion and extramural venous invasion.…”
Section: Dwi For Follow Up After Treatmentmentioning
confidence: 94%
“…Around half of these reports found significant correlations between DWI-derived parameters and clinical or histopathology outcomes. 96,[102][103][104][105][106][107][108][109][110][111] Of those studies that found significant results, the majority reported low ADC values for the unfavourable outcome groups (e.g. higher TN-stage, lower differentiation grade, MRF+ stage and extranodal tumour deposits), and high ADC values for the more favourable outcome groups, suggesting that tumours with a more dense cellular structure (low ADC) tend to show a more aggressive growth pattern.…”
Section: Dwi For Follow Up After Treatmentmentioning
confidence: 99%
“…D was more likely to be related to cellular microstructure than to tumor cellularity[ 11 ], and D* actually reflected blood flow and was affected by flow velocity and vascular geometry[ 34 ]. IVIM-DWI–derived parameters were also useful for describing rectal tumor aggressiveness and prognosis[ 31 ]. D* and f tended to increase with greater tumor differentiation, and D and D* decreased with advanced tumor stages.…”
Section: Colorectal Tumorsmentioning
confidence: 99%
“…The f is the partial volume of the whole capillary vascular fraction[ 9 ] and the proportion of the arterial blood is greater than the venous component for f at low b values[ 35 ]. This phenomenon is reflected in well-differentiated tumors and poorly differentiated tumors: the capillary vascular network is relatively mature in the former, and there is poor structure of luminal vessels leading to low perfusion of the microcirculation in the latter[ 31 ]. This could be confirmed by the correlation between the D*, f and MVD in colorectal tumors[ 13 ].…”
Section: Colorectal Tumorsmentioning
confidence: 99%
See 1 more Smart Citation